The effects of school poverty on adolescents’ sexual health knowledge - Atkins, Robert (2012)
Using National Longitudinal Study of Adolescent Health data, hierarchical linear modeling was conducted to estimate the association of school poverty concentration to the sexual health knowledge of 6,718 adolescents. Controlling for individual socio-economic status, school poverty had modest negative effects on sexual health knowledge. Although not directly associated with sexual health knowledge, after controlling for demographic characteristics, school poverty interactions showed that sexual health knowledge was associated with higher grade point average (GPA) and age. The combination of low GPA and high-levels of school poverty was especially detrimental for students’ sexual health knowledge. There are differences in the sexual health knowledge of adolescents attending low poverty and high poverty schools that can be attributed to the school environment.